Impact on medical practice of accessing pharmaceutical records. (January 2019) - Gillibert, André; Griffon, Nicolas; Schuers, Matthieu; Hardy, Kristell; Elmerini, Amine; Letord, Catherine; Staccini, Pascal; Darmoni, Stefan J.; Benichou, Jacques; ,
Highlights: The Pharmaceutical Record System contains information not found elsewhere. Information contained in the Pharmaceutical Record System may modify patient's management. More than half of the French population has a pharmaceutical record. Abstract: Introduction: The pharmaceutical record system (PRS) is a French nationwide centralized electronic database shared among all community pharmacists listing all drugs dispensed by community pharmacists in the last four months. The objective of this study, the Medication Assessment Through Real time Information eXchange - Distributed Pharmaceutical Record System (MATRIX - DPRS) study, was to assess the clinical impact of the PRS upon granting access to physicians in three hospital specialties: anesthesiology, emergency medicine and geriatrics. Material and methods: A multicenter prospective study was conducted in six hospital departments, two per specialty. Participating physicians noted medication information found exclusively in the pharmaceutical record (PR) of each patient unavailable elsewhere and any diagnostic or therapeutic management changes resulting from the PR information. The primary objective was to assess the proportion of diagnostic or therapeutic management changes attributable to the PR among patients who had an accessible PR. Results: The inclusion level ranged from 1.1 to 30% in the six departments. The rate of diagnostic or therapeutic management changes was highest in geriatrics (n = 31/67; 46.3% 95% Confidence IntervaI (CI): 34.0–58.9%) and lowest in anesthesiology (n = 36/227; 15.9% 95% CI: 11.4–21.3%). Emergency medicine was intermediate (n = 5/22; 22.7% 95% CI: 7.8–45.4%). Conclusion: Although the inclusion rate and statistical precision were low, these findings suggest that the information contained in the PRS is useful and may result in modifying patient management in a sizeable proportion of patients. This opens the prospect of evaluating other hospital specialties, as well as primary and secondary care settings.